Towards smart self-clearing glaucoma drainage device. (December 2018) - Park, Hyunsu; Raffiee, Amir; John, Simon; Ardekani, Arezoo; Lee, Hyowon
Abstract For patients who are unresponsive to pharmacological treatments of glaucoma, an implantable glaucoma drainage devices (GDD) are often used to manage the intraocular pressure. However, the microscale channel that removes excess aqueous humor from the anterior chamber often gets obstructed due to biofouling, which necessitates additional surgical intervention. Here we demonstrate the proof-of-concept for smart self-clearing GDD by integrating magnetic microactuators inside the drainage tube of GDD. The magnetic microactuators can be controlled using externally applied magnetic fields to mechanically clear biofouling-based obstruction, thereby eliminating the need for surgical intervention. In this work, our prototype magnetic microactuators were fabricated using low-cost maskless photolithography to expedite design iteration. The fabricated devices were evaluated for their static and dynamic mechanical responses. Using transient numerical analysis, the fluid–structure interaction of our microactuator inside a microtube was characterized to better understand the amount of shear force generated by the device motion. Finally, the anti-biofouling performance of our device was evaluated using fluorescein isothiocyanate labeled bovine serum albumin. The microactuators were effective in removing proteinaceous film deposited on device surface as well as on the inner surface of the microchannel, which supports our hypothesis that a smart self-clearing GDD may be possible by integrating microfabricated magnetic actuators in chronically implanted microtubes. Actuators: Glaucoma drainage devices The addition of a magnetically powered microdevices inside the tube of a glaucoma drainage device enables the removal of debris caused by biofouling without surgery. Patients suffering from glaucoma often require the insertion of a drainage device to remove excess aqueous humor from the eye, so that the intraocular pressure does not reach a level that could damage the optic nerve. However, the microtubes that these devices contain often become blocked as a result of biofouling, requiring the patient to undergo an operation. Now, a team led by Hyowon Lee from Purdue University, USA, integrate microactuators that can be activated using an externally applied magnetic field, removing the build-up of debris without invasive surgery.